Dietary supplementation of lemon verbena (Aloysia citrodora) improved immunity, immune-related genes expression and antioxidant enzymes in rainbow trout (Oncorrhyncus mykiss). Issue 99 (April 2020) - Hoseinifar, Seyed Hossein; Shakouri, Meysam; Doan, Hien Van; Shafiei, Shafigh; Yousefi, Morteza; Raeisi, Mojtaba; Yousefi, Samira; Harikrishnan, Ramasamy; Reverter, Miriam
Abstract: The use of veterinary drugs for the treatments of fish diseases has often health and environmental side effects and thus alternative more sustainable strategies are needed. In this study we have explored the effect of dietary administration of lemon verbena ( Aloysia citrodora ) leaves powder on growth, immune parameters and antioxidant enzyme activity of rainbow trout ( Oncorrhyncus myskiss ). The results show that adding lemon verbena (LV) leaves powder (0.5, 1 and 2%), as feed supplement does not affect significantly rainbow trout growth, but increases the levels of some immune parameters. All enriched-diets induced an increase in the levels of lysozyme activity and total immunoglobulin in rainbow trout serum (P < 0.05), whilst 1 and 2% enriched-diets increased lysozyme and immunoglobulin in skin mucus. Expression of interleukin-1β ( IL-1β ) was enhanced in all fish supplemented with LV leaves powder (0.5, 1 and 2%) whilst only the diet with the highest dose (2%) induced a significantly higher expression of IL-8 and tumour necrosis factor ( TNF-α ). Fish fed with LV leaves powder at 1 and 2% had significantly lower expression of transforming growth factor ( TGF-β, P < 0.05). Furthermore, all enriched-diets significantly increased the activity of super oxide dismutase (SOD, P < 0.05) and diets containing 1 and 2% of LV leaves powder also increased activity of glutathione-S-transferase (GST) and glutathione peroxidase (GPx). In conclusion, LV leaves powder administered as feed supplement at 2% enhances the expression of some immune-related genes ( IL-1β, IL-8 and TNF- α ), rises the levels of lysozyme and total immunoglobulin in serum and skin mucus and increases the activity of antioxidant enzymes (SOD, GST and GPx) in rainbow trout. Highlights: Dietary lemon verbena ( Aloysia citrodora ) leaves powder increased serum immune parameters in trout fingerlings. Trout fingerlings fed LV leaves powder showed altered mucosal immunity. Feeding on LV leaves powder significantly increased the antioxidant enzymes activity. Immune related genes were up-regulated in LV leaves powder fed trout.